Actividad antifúngica del extracto de lechosa (euphorbia hirta) para el control de la moniliasis (Moniliophthora roreri) del cacao (Theobroma cacao L.) - Díaz Mendoza, Katia Anabel (2021)
Cacao fields (Theobroma cacao L.) are constantly affected by diseases that can considerably compromise its production, including moniliasis (Moniliophthora roreri). The search for alternative control measures that allow reducing its presence in the field is imperative, therefore, the aim of this research was to evaluate the effect of Euphorbia hirta extract on M. roreri pathogen of cacao. The study had two phases: in vitro and in vivo. The experiment at in vitro conditions was established under a completely randomized design with treatments using different concentrations of the extract (1, 2, 3, 4, 5, 6, 7, 8 and 9%) to modify the culture medium and a control (T0). Spore germination and mycelium growth of M. roreri were evaluated. The results revealed that the extract of E. hirta at 9% v/v was the one who succeeded in inhibiting 100% of spore germination and 79.78% of mycelial growth. In the field trial, a completely randomized block design was used where three treatments were applied to the fruits (under three months) and a control: E. hirta extract with concentrations of 10% (T1) and 5% (T2), a chemical control based on copper oxide (T3) and the control (T0). The trees treated with the extract of E. hirta at 10% presented lower percentages of fruits infected by M. roreri and other pathogens compared to the other treatments. Similarly, the percentage of healthy fruits in T1 was higher than the other treatments. These results show the potential of species such as E. hirta to be used as a source of compounds that are used as tools that help reduce the impact of M. roreri in cacao fields. Keywords: disease management, plant extracts, inhibition, in vitro.